A Normative Juridical Review on the Implementation of Smoke-Free Area Policy at RSUD Hj. Anna Lasmanah Banjarnegara - Ikhwan, Dwika Yulansyah Nur (UM Purwokerto Press, 2023)
The implementation of smoke-free area policies has become a primary focus in efforts to protect public health from the adverse effects of cigarette smoke. This study aims to conduct a normative juridical review of the implementation of the smoke-free area policy at RSUD Hj. Anna Lasmanah Banjarnegara. The normative juridical analysis method is used to evaluate the effectiveness of the policy implementation. The normative juridical approach involves analyzing the relevant legal framework, particularly Banjarnegara District Regulation No. 3 of 2019 concerning Smoke-Free Areas. This analysis encompasses key aspects of the regulation, such as the designation of smoke-free zones, penalties for violators, and related law enforcement mechanisms. The findings of the normative juridical review indicate that the implementation of the smoke-free area policy at RSUD Hj. Anna Lasmanah Banjarnegara has made significant progress. However, challenges remain in terms of implementation and law enforcement. These challenges include raising public awareness and compliance, resource limitations, and effective coordination among stakeholders. Based on these findings, this study provides recommendations for RSUD Hj. Anna Lasmanah Banjarnegara and relevant parties. The recommendations include policy improvements to enhance the effectiveness of smoke-free zones, enhanced law enforcement measures, and other supportive efforts such as intensive public awareness campaigns and education. In conclusion, this normative juridical review provides an overview of the implementation of the smoke-free area policy at RSUD Hj. Anna Lasmanah Banjarnegara. Despite the challenges that need to be addressed, this policy makes a significant contribution to protecting public health and promoting behavioral changes related to smoking. Collaborative efforts and strategic measures are needed to enhance the effectiveness of this policy and ensure comprehensive public health protection.